Analysis performance of quality of service (QoS) IP VPN (internet protocol virtual private network) / Siti Fuwaizah Mohd Ghazali - Mohd Ghazali, Siti Fuwaizah (2006)
Next generation IP based networks are heading into the multiservice markets which provide multiple service classes over an IP network. Quality of Service (QoS) of Internet Protocol Virtual Public Network (IP VPN) is a set of requirements that the network must meet to ensure a service level for each type of traffic. A private IP based network infrastructure is a network service that is able to prioritize traffic according to the application's importance using advanced Multi Protocol Label Switching (MPLS) technology. This technology enables secure and reliable performance levels. Private-based MPLS network provides better QoS compared to public networks.